Representation of racialised and ethnically diverse populations in multicentre randomised controlled trials of GLP-1 medicines for obesity: a systematic review and meta-analysis of gaps - Ravi Retnakaran; Caroline K Kramer; Lisa Richardson; Yaanu Jeyakumar; Shohinee Sarma (BMJ Global Health)
Introduction Trials of GLP-1 (glucagon-like peptide-1) medicines have changed the paradigm of obesity treatment. Diversity in trial participation is imperative considering that obesity disproportionately impacts marginalised populations worldwide. We performed a systematic review and meta-analyses to evaluate the representation of racialised and ethnically diverse populations in randomised controlled trials (RCTs) of GLP-1 medicines for obesity.Methods We searched PubMed/Embase/ClinicalTrials.gov. Prevalence of each racial/ethnic group was compared in relation to the USA, Canada, the UK, Brazil and South Africa. The geographical locations of the trial sites were extracted.Results 27 RCTs were identified (n=21 547 participants). Meta-analyses of prevalence demonstrated the vast predominance of white/Caucasians (79%) with smaller proportion of blacks (9%), Asians (13%), Indigenous (2%) and Hispanics (22%). The gaps in representation were evidenced by the significantly under-represented proportion of non-white individuals in these RCTs as compared with the prevalence of non-white individuals in the general population of the USA (−23%, p=0.002) and Canada (−34%, p<0.0001), reaching an alarming gap of −58% in relation to Brazil and striking under-representation of −68% as compared with South Africa. Similar discrepancies in proportions of blacks, Asians and Indigenous peoples as compared with reference nations were found. Moreover, the trial sites (n=1859) were predominately located in high-income countries (84.2%), in sharp contrast to the global prevalence of obesity that is predominantly in low-income and middle-income countries.Conclusion There are discrepancies in representation of racialised and ethnically diverse populations in obesity trials as compared with multiethnic populations worldwide. These data highlight the need for broader reform in the research process in order to ultimately address health inequities.